The Joy of Takings - Michael M. Berger (Washington University Journal of Law & Policy, 2017)
This Essay discusses the various circumstances under which Takings Law can be litigated. Beginning with an analysis of his personal experience in litigation, Berger details significant developments in Takings Law and posits on their future in a rapidly advancing technological sphere. Berger closes by analogizing airport takings law to issues involving drones and speculates that the intersection between drones and the law will mirror that of prior takings lawsuits.
Keywords: Takings Law; litigation; airport takings law; drones; Los Angeles; U.S. Supreme Court; Washington University Law School; California